PENGEMBANGAN MODUL MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN KOGNITIF KOMPREHENSIF DAN PROBLEM SOLVING SISWA - Desi Nur Fitriani; Netriwati; Hasan Sastra Negara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of mathematics modules based on the Time Token learning model in enhancing students’ comprehensive cognitive abilities and problem-solving skills. The background of this research stems from the need for instructional strategies that promote active participation, critical thinking, and equitable student engagement—particularly in mathematics, a subject often perceived as abstract and challenging. The Time Token model was selected for its ability to foster a structured and cooperative learning environment that ensures fair communication among students. A quasi-experimental method was employed using a pretest-posttest control group design. The sample consisted of two experimental groups: a large group and a small group, both utilizing mathematics modules integrated with the Time Token approach. Research instruments included cognitive tests, problem-solving assessments, and student interest questionnaires. The findings revealed statistically significant improvements in both comprehensive cognitive skills and problem-solving abilities among students in both experimental groups. These results indicate that mathematics modules incorporating the Time Token model are effective in enhancing learning quality and fostering higher-order thinking competencies. The study recommends broader implementation and teacher training to support successful adoption across various educational levels and contexts.